Institutions, governance and incentives in common property regimes for African rangelands - Swallow, B.M.; Bromley, D.W. (Springer, 1995)
The general distinctions between open access, state property, common proerty and private property are now well established in the academic literature. When applied to African rangelands, however, common property admits a wide variety of resource management regimes. To formulate effective policies it is necessary to understand the structure and operations of particular regimes. In this paper we discuss three examples of common property regimes, two from the southern African nation of Lesotho and one from the west African nation of Senegal, to illustrate some of the key characteristics of common property regimes. In particular, it is important to understand the structure of governance, the types of institutions that govern behavior, and the compatibility between governance, institutions and individual incentives. A common property regime can only be effective if its institutionsare compatible with the structure of governance. The extent of its effectiveness also depends upon the incentives and expectations of individuals expected to enforce the rules of the institutions or comply with their terms. At present, most African governments lack the organizational capacity and political will necessary to implement state property regimes, official regulations on resource use, or individual property rights for rangelands resources. In many cases it is more appropriate for governments to define and enforce group rights to particular resources, then help to establish conditions in which internal group dynamics yield efficient resource management outcomes.